Humanity : A History of European Concepts in Practice From the Sixteenth Century to the Present - Bethencourt, Francisco; Betts, Paul; Grigore, Mihai-D.; Delgado, Mariano; Becker, Judith; Brier, Robert; Weller, Thomas; Lingen, Kerstin von; Möller, Esther; Berger, Joachim; Stornig, Katharina; Kruip, Gerhard (2016)
This volume investigates the development of the concepts and practices of “humanity” from the sixteenth century up to the present. By taking a comparative and interdisciplinary approach, the contributers focus on Europe as well as Europe’s relations to other world regions in the process that shaped “humanity”. They show how this emerging concept led to the overcoming of fundamental divisions in many spheres on the one hand and the formation of new hierarchies on the other.